Analysis of aerodynamic torques affecting dust particle orientation as input to microwave cross polarization - Abdulwaheed , Musa; Saad Osman, Bashir; Sameir, Ali (IEEE, 2013)
Cross polarization in microwave link, method of using dual orthogonal polarizations to optimally conserve the frequency spectrum, has received considerable interest in the recent time. This paper implicitly discusses its prediction in sand and dust storms. Cross polarization in dust storms occurs due to the non-sphericity of the falling dust particles and the tendency of the particles to align in a particular direction at a time (canting angle). It is therefore important to have adequate information on the dust particle sizes, particle shapes, orientation of particles along the propagation path etc. for the cross polarization due to dust storms. This work deals with the latter two points by making use of a more reliable measure of turbulence shear and inertial torque to tackle orientation of sand and dust storms suspended particles calculations as input to cross polarization discrimination magnitudes. The paper explicitly analyses the systematic alignment of particles due to torque of fluid flow round dust particles as a main parameter causing cross polarization. The results obtained show that there exists some form of systematic alignment of particles in the most relevant size range that was considered.